2014
DOI: 10.1016/j.ymeth.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for exploring TGF-β signaling in Drosophila

Abstract: The TGF-beta pathway is an evolutionarily conserved signal transduction module that mediates diverse biological processes in animals. In Drosophila, both the BMP and Activin branches are required for viability. Studies rooted in classical and molecular genetic approaches continue to uncover new developmental roles for TGF-beta signaling. We present an overview of the secreted ligands, transmembrane receptors and cellular Smad transducer proteins that comprise the core pathway in Drosophila. An assortment of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 124 publications
(190 reference statements)
1
43
0
Order By: Relevance
“…43 BMP ligands bind the type I serine-threonine receptors Thickveins (Tkv) and Saxophone (Sax) to induce C-terminal phosphorylation of the R-Smad Mothers against DPP (Mad). 44,45 TGF-b/Activin ligands signal through splice isoforms of the Baboon receptor to activate the R-Smad dSmad2 (Smad on X).…”
Section: Resultsmentioning
confidence: 99%
“…43 BMP ligands bind the type I serine-threonine receptors Thickveins (Tkv) and Saxophone (Sax) to induce C-terminal phosphorylation of the R-Smad Mothers against DPP (Mad). 44,45 TGF-b/Activin ligands signal through splice isoforms of the Baboon receptor to activate the R-Smad dSmad2 (Smad on X).…”
Section: Resultsmentioning
confidence: 99%
“…Molecular and functional analysis of TGF-β signaling core components in model systems has the potential to provide a deep understanding of their activity and exact role in modulating a diverge range of physiological processes as well as controlling different steps of complex interactions within the organism (Li et al, 2006). In the fruit fly D. melanogaster , the Activin and BMP signals are transduced via receptor and Smad phosphorylation events that are essentially identical to those described for vertebrate TGF-β family signaling (Zi et al, 2012; Peterson and O’Connor, 2014). Interestingly, it was previously shown that TGF-β superfamily signals modulate the D. melanogaster immune response to wounding and bacterial infection (Clark et al, 2011).…”
Section: Introductionmentioning
confidence: 89%
“…TGF-β ligands are evolutionary conserved signaling modules present in all metazoans and the closest conserved homologs of the mammalian GDNF family (Peterson and O’Connor, 2014; Saarma, 2000). So far, only activin has been implicated in the regulation of dendritic organization by restricting dendritic field size of amacrine cells through TGF-β signaling (Ting et al, 2014), whereas Mav can act as a glial-derived cue regulating neuromuscular junction (NMJ) growth (Fuentes-Medel et al, 2012).…”
Section: Discussionmentioning
confidence: 99%